KERJA SAMA INDONESIA-KOREA SELATAN DALAM MENINGKATKAN KUALITAS INDUSTRI KREATIF ANIMASI INDONESIA (2018-2022) - Caisar Febryani (2023)
The rapid growth of creative industries has made countries realize this opportunity. Indonesia is experiencing growth in the animation creative industry sector, while South Korea has established policies to support the growth of its creative industry. Similar purposes lead them to make international cooperation in the creative industries field, especially in the sub-sector of Animation, to increase the quality of the Animation creative industries sector. Researchers used the concept of bilateral cooperation and creative industries with qualitative descriptive research methods and data collection methods through literature reviews. This research aims to determine the realized form of cooperation between Indonesia and South Korea in the creative industries of the Animation sub-sector. The results of this study indicate that the form of implementation of this collaboration is able to improve the quality of Indonesia's creative animation industry with softness such as the screening of the Indonesian animated film 'Nussa' at BIFAN 25th in South Korea, the joint production of the animated character IP 'Little Dreamer Gguda,' and the signing of several MoU between animation studios and associations